OPTIMIZATION OF THE MANAGEMENT PROCESS OF A SHIPPING COMPANY - Тимощук, О. М.; Іваненко, В. М.; Медведева, О. Ю. (Science-based technologies, 2019)
In an unstable environment, in situations where an enterprise needs to take a decision regarding the increase in the efficiency of its activities, the relevance of continuous planning of operational activities of shipping companies becomes more than obvious. The article is devoted to the research and use of management problems in the transport process, the substantiation of the necessity of implementing optimization solutions in the management of the shipping company’s work on the basis of the use of modern communication facilities, as well as the change of the general approach to the role of plans of different levels in conditions of instability of the external environment. By changing the input parameters of the scheduling task, its individual characteristics or the interrelations of the elements of the system, it is possible to obtain different output results that are analyzed, and then management decisions are made. In this case, it is possible to establish functional relationships between the output parameters and the individual characteristics and parameters of the system, as well as the dependence of decision-making results on the mode of operation of the shipping in different operating conditions. Consequently, the implementation of the main tasks of continuous planning in the activities of shipping companies will contribute to the timely and qualitative fulfillment of the main goal - to optimize the process of managing a shipping company, facing water transport and should be achieved at the lowest cost of material and financial resources. It is proved that in the conditions of the intensive development of information technologies that allow solving any complex problems at the expense of the automation of progressive is the tendency of integration and automation of all functions on the vessel, including its tasks of controlling the technical condition of the vessel. Thus, the scientific task of developing models and methods of automation of the technical condition of water transport facilities in various conditions of operation in order to implement them in mathematical and software systems in the Integrated Bridge System is new and relevant.